Floristic Inventory of The Proposed Site for Tarsier Tourism Center in Villa Aurora, Bilar, Bohol, Philippines - Tomas D Reyes Jr; Jeralyn D Abadingo; Shiela G Tabuno; Eunice K L Serino; Joecel B Mabanag; Rizaldy C Merdacal (Jurnal Ilmu Kehutanan)
The study assessed the present vegetation composition of the Proposed Site for the Tarsier Tourism Center (PTTC) at Villa Aurora, Bilar, Bohol and performed a comparative analysis with the existing Tarsier Sanctuary (TS) at Canapnapan, Corella, Bohol. The basis for comparison was the computed importance values, species richness, species dominance, and percent distribution of plants according to self-defined DBH classes. Results showed that both sites had very high species richness and evenness values. Common overstorey and understorey plant species found in both areas were katagpo (Psychotria sp.), sagimsim (Syzygium brevistylum [C. B. Rob]Merr.) and bagauak (Clerodendrum minahassae Teijsm. & Binn.). Apart from sagimsim (Syzygium brevistylum [C.B.Rob.] Merr.), selaginella (Selaginella cuppresina Lin.), and lunas (Lunasia amara Blanco) were also common in the ground vegetation of both areas. Percent distribution of trees according to self-defined DBH classes revealed that PTTC had 87.55% of the total recorded plants with DBH measurements of <10 cm. Our data was found lower by almost 10% from TS. Considerable percentages of trees were also shared in other DBH classes for PTTC. DBH class range of 10-20 cm had 6.88%, while 5.58% was computed for DBH class of >20 cm. Percent distribution of trees on these DBH ranges (especially on DBH class >20 cm) indicated the presence of medium and large trees. The largest DBH measured in the PTTC was 70 cm while in TS was only 22 cm. The proposed 10-ha site in Villa Aurora, Bilar, is suited to be utilized as Tarsier Tourism Center. In case the proposed project is to be pursued, enclosure similar to what has been constructed in Canapnapan, Corella, Bohol, Philippines should also be established to prevent stray animals from predating the captive tarsiers.